2011
DOI: 10.1039/c1cc15557a
|View full text |Cite
|
Sign up to set email alerts
|

Halichonines A, B, and C, novel sesquiterpene alkaloids from the marine sponge Halichondria okadai Kadota

Abstract: Novel sesquiterpene alkaloids, halichonines A (1), B (2), and C (3), were identified from the marine sponge Halichondria okadai Kadota. By spectroscopic analyses and synthesis, their structures were revealed to include a 6,6-bicyclic ring system and two prenylated amine moieties. In addition, 2 induced apoptosis in HL60 human leukemia cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Compound 325 displayed broad cytotoxicity against four cancer cell lines, including A549, SK-OV-3, SK-MEL-2, and HCT-15, with IC 50 values of 2.0, 1.9, 3.9 and 3.2 µM, respectively [76]. Noveliresane sesquiterpene alkaloids, halichonines A (327), B (328), and C (329) (Figure 8), were identified from the marine sponge Halichondria okadai Kadota, and 328 wasthen subjected to the trypan blue dye exclusion using HL60 human leukemia cells, and showed cytotoxicity (IC 50 value: 0.60 µg/mL) [77]. One γ-elemene-type sesquiterpenes, 8β(H)-elema-1,3,7(11)-trien-8,12-lactam (330) (Figure 8) was obtained from the rhizomes of Curcuma phaeocaulis [63].…”
Section: Germacrane Elemaneand Iresane Sesquiterpenoidsmentioning
confidence: 99%
“…Compound 325 displayed broad cytotoxicity against four cancer cell lines, including A549, SK-OV-3, SK-MEL-2, and HCT-15, with IC 50 values of 2.0, 1.9, 3.9 and 3.2 µM, respectively [76]. Noveliresane sesquiterpene alkaloids, halichonines A (327), B (328), and C (329) (Figure 8), were identified from the marine sponge Halichondria okadai Kadota, and 328 wasthen subjected to the trypan blue dye exclusion using HL60 human leukemia cells, and showed cytotoxicity (IC 50 value: 0.60 µg/mL) [77]. One γ-elemene-type sesquiterpenes, 8β(H)-elema-1,3,7(11)-trien-8,12-lactam (330) (Figure 8) was obtained from the rhizomes of Curcuma phaeocaulis [63].…”
Section: Germacrane Elemaneand Iresane Sesquiterpenoidsmentioning
confidence: 99%
“…The Halichondria genus consists of over 60 species and, over the years, novel and bioactive metabolites of varying structural classes and pharmacological activities have been isolated from this genus. Structural classes range from macrolides, sequiterpenes, polyethers, alkaloids and sterols with a dominance in anti-tumour activities [44][45].…”
Section: Genus: Halichondriamentioning
confidence: 99%
“…Halichonine B was then subjected to the trypan blue dye exclusion using HL-60 human leukemia cells, and has shown cytotoxicity at IC 50 value of 0.6 µg·mL −1 . DNA ladder analysis revealed that halichonine B has induced DNA fragmentation in HL-60 cells [ 127 ].…”
Section: Porifera Involved In the Biosynthesis Of Cytotoxic Metabomentioning
confidence: 99%